Physics Module Design of Measurement Subject under Constructivism Approach - Sigit Dwi Saputro; Suparmi Suparmi; Cari Cari; Aisyah Fidiyah; Titin Sandias Budi Ningsih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
This aim of the research is to make valid, practical, and effective constructivism learning. The development of constructivism learning module applies Borg's research procedure theory, basically consisting of: (1) preliminary study and data collection, (2) planning, (3) developing initial product, (4) limited testing, (5) revising product (6) conducting field tests, (7) revising the operational product, (8) conducting operational field tests, (9) revising the final product, and (10) eliminating and implementing the product. This module is for class X students on the subject of measurement. Students will be able to learn independently by constructivist principles. The results of this study include (1) Creation of constructivism learning module from requirement analysis, module design, expert validation, small-scale module test revision, large-scale module test revision. (2) the feasibility of constructivism learning module that includes physics constructivism learning module on measurement material in the expert test included in the valid category and without revision with percentage level 76%. Student responses on the small-scale test as well as large-scale test get the positive response.